La disfemia en el rendimiento académico de lengua y literatura en el tercer año EGB, UEVHAM parroquia Zhud, Cañar 2020-2021 - Calle Guallpa, María Isolina (2022)
Dysphemia is one of the main causes of poor academic performance in the area of language and literature since it constitutes a deficiency in oral expression, which can cause alterations in reading, also makes it impossible to develop their abilities and cognitive skills normally; that is why dysphemia cannot be delimited as a simple oral language disorder produced by a linguistic cause identified in reading or communication, but must be configured as a process of integral intervention. In this way, the objective of this study is to analyze dysphemia in the academic performance of Language and Literature through field research, in order to establish solution strategies in children's learning; for this research to be carried out, the deductivemethod wasused, which consists of drawing a conclusion based on a particular premise; the same way is made use of the inductive method since this work starts from a previous documentary-bibliographic research to be able to create solid conclusions on the subject addressed,as well as the analytical method wasimplemented, since it is the only method that allows a cautious inquiry on each of the factors that influence the development of speech disorder in the children and finally the synthetic method was used, since through it we can unite, collect relationships and characteristics that the study phenomenon demands. To obtain results, a survey was implemented with the teacher of the area of language and literature where it was determined that seven of her students suffered from dysphemia, in this virtue these students were followed up and a didactic guide was designed with playful activities as a solution strategy to help treat dysphemia. Finally, the teacher is recommended to apply this guide continuously to see effective results in children who suffer from it as well as new researchers are invited to continue updating information about this common disorder that develops daily in educational institutions.